Analysis of Plot of Syngeâ€™s Play â€œRider to the Seaâ€ - Siahaan, Safnidar (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2016)
The research offers a plot analysis in Syngeâ€™s play â€œRider to the Seaâ€. This play is written in 1902 describing a complex family life story. This play will be analyzed by using the structure method focusing on the plot development of the play. The story of the play "Rider to the Sea" is interesting since it portrays the different side of family where the family life is still dependent on the menâ€™s efforts in their family. Roles of the men in the story are very important because the family life cannot run well without menâ€™s contribution. The Riders to the Sea has a unique place in dramatic history. The essence of its uniqueness lies in the creation of a true tragedy within its boundaries of a one act play. At first sight, the plot would seem too trivial and the characterization too faintly sketched to enable the playwright to build up and communicate the typical momentum of a high tragedy. To reach the aim of the analysis, the writer uses the qualitative research. The result is expected to give the reader a better understanding of the description of the plot of the play â€œRider to the Sea.â€Â Keywords : plot, simple plot, complex plot